Green Accounting and Malang Hospitality Industry: A Inevitability - Annisa Rizkaninghadi Imansari; Roekhudin Roekhudin; Yeney Widya Prihaningtias (Jurnal Economia, 2019)
Abstract: This research aims to study the implementation of green accounting on the hospitality industry in Malang based on internal and external perspectives. This type of research is a multi-case study. Data collection was conducted in 2018 through interviews with internal parties of Harris Hotel (five stars), The Balava Hotel (four stars), and ubud Hotel and Cottages (three stars); guests and people around the hotels and environmental Services in Malang; observation and documentation. The results of this research show that three, four, and five stars hotels in Malang have implemented green accounting very well. All of those hotels also spent some expenses on the environment to reduce the risk of pollution and environmental damage. From the external perspective, no one is feeling disadvantaged from the activities of hotel operational. In the future, the hotels are expected to improve their awareness on the environment. Keywords: Green Accounting, Environmental CostAkuntansi Hijau dan Industri Perhotelan: Sebuah KeniscayaanAbstrak: Penelitian ini bertujuan untuk mengetahui penerapan akuntansi hijau pada industri perhotelan di Kota Malang dari perspektif internal dan eksternal. Jenis penelitian ini adalah multi studi kasus. Pengumpulan data dilakukan pada tahun 2018, melalui wawancara dari pihak internal Hotel Harris (bintang lima), The Balava Hotel (bintang empat), dan Ubud Hotel Cottages (bintang tiga); tamu dan masyarakat sekitar dari ketiga hotel, pihak Dinas Lingkungan Hidup Kota Malang; observasi dan dokumentasi. Hasil penelitian ini menunjukkan bahwa hotel bintang tiga, empat dan lima di Kota Malang telah menerapkan beberapa aktivitas akuntansi hijau. Ketiga hotel juga telah mengeluarkan beberapa biaya lingkungan dalam rangka mengurangi risiko pencemaran dan kerusakan lingkungan. Dari sisi eksternal, tidak ada pihak yang merasa dirugikan dari aktivitas operasional hotel, ke depannya diharapkan hotel dapat lebih peka terhadap lingkungan. Kata Kunci: Akuntansi Hijau, Biaya Lingkungan